The Effect of Product Quality Management on the Accounting Performance of Small and Medium Companies - Kadhim, Salam Radhi; Ahmed, Ammar Hussein; Radhi, Aeshah Hasan (South Asian Journal of Social Sciences and Humanities, 2024)
This research aims to study product quality management and its influence on the accounting performance of medium and small companies. This was done using 116 Asian small and medium companies from 2020 to 2023 in the study. The results determined that there is a positive and strong association between product quality management and the accounting performance of medium and small companies. The product quality management technique is reflected among the recent methods that an companies cans face with the present international technological revolution and the strong competition that characterizes big economies proposed by the nature of the globalization and challenge. The study at hand aims to know the role that product quality management plays in improving performance. Product quality practices affect accounting performance in light of the presence and types of innovation, radical product innovation, process innovation, requires more work to improve product quality.